(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
MTs Nurusy Syifa is an educational institution under the auspices of the Ministry of Religion located in Bekasi City. In order to improve the quality of education, this school routinely evaluates the performance of educators. However, the process of evaluating the best teachers applied is still manual. This method has weaknesses such as subjectivity, time inefficiency, and limitations in data storage and processing. This study aims to analyze the existing problems and design a decision support system (DSS) based on the SMART (Simple Multi-Attribute Rating Technique) method to help the teacher evaluation process more objectively, transparently, and efficiently. This system was developed using the PHP programming language and MySQL database. The development method used is waterfall, with a Unified Modeling Language (UML) modeling approach that includes use case diagrams, activity diagrams, and class diagrams. The results of this study are in the form of a decision support system design that is able to manage teacher assessment data based on a number of criteria, such as discipline, responsibility, mastery of material, and teaching methods, and produce reports of the best teachers that can be used as a basis for decision making by the school. Keywords: Decision Support System, SMART Method, Teacher Assessment, web. Abstrak MTs Nurusy Syifa merupakan institusi pendidikan di bawah naungan Kementerian Agama yang berlokasi di Kota Bekasi. Dalam rangka meningkatkan mutu pendidikan, sekolah ini secara rutin melakukan evaluasi terhadap kinerja tenaga pendidik. Namun, proses penilaian guru terbaik yang diterapkan masih bersifat manual. Metode tersebut mengandung kelemahan seperti subjektivitas, inefisiensi waktu, serta keterbatasan dalam penyimpanan dan pengolahan data. Penelitian ini bertujuan untuk menganalisis permasalahan yang ada serta merancang sistem pendukung keputusan (SPK) berbasis metode SMART (Simple Multi-Attribute Rating Technique) guna membantu proses evaluasi guru secara lebih objektif, transparan, dan efisien. Sistem ini dikembangkan menggunakan bahasa pemrograman PHP dan database MySQL. Metode pengembangan yang digunakan adalah waterfall, dengan pendekatan pemodelan Unified Modeling Language (UML) yang meliputi use case diagram, activity diagram, dan class diagram. Hasil dari penelitian ini berupa rancangan sistem pendukung keputusan yang mampu mengelola data penilaian guru berdasarkan sejumlah kriteria, seperti disiplin, tanggung jawab, penguasaan materi, dan metode mengajar, serta menghasilkan laporan guru terbaik yang dapat dijadikan dasar dalam pengambilan keputusan oleh pihak sekolah. Kata kunci: Sistem Pendukung Keputusan, Metode SMART, Penilaian Guru, web.